Self‐Supported FeP‐CoMoP Hierarchical Nanostructures for Efficient Hydrogen Evolution. Issue 10 (14th April 2020) - Wang, Qin; Wang, Zhiying; Zhao, Yue; Li, Fumin; Xu, Ling; Wang, Xiaoming; Jiao, Huan; Chen, Yu
Abstract: Fabricating highly efficient electrocatalysts for electrochemical hydrogen generation is a top priority to relief the global energy crisis and environmental contamination. Herein, a rational synthetic strategy is developed for constructing well‐defined FeP−CoMoP hierarchical nanostructures (HNSs). In general terms, the self‐supported Co nanorods (NRs) are grown on conductive carbon cloth and directly serve as a self‐sacrificing template. After solvothermal treatment, Co NRs are converted into well‐ordered Co−Mo nanotubes (NTs). Subsequently, the small‐sized Fe oxyhydroxide nanorods arrays are hydrothermally grown on the surface of Co−Mo NTs to form Fe−Co−Mo HNSs, which are then converted into FeP−CoMoP HNSs through a facile phosphorization treatment. FeP−CoMoP HNSs display high activity for hydrogen evolution reaction (HER) with an ultralow cathodic overpotential of 33 mV at 10 mA cm −2 and a Tafel slope of 51 mV dec −1 . Moreover, FeP−CoMoP HNSs also possess an excellent electrochemical durability in alkaline media. First‐principles density functional theory (DFT) calculations demonstrate that the remarkable HER activitiy of FeP−CoMoP HNSs originates from the synergistic effect between FeP and CoMoP. Abstract : FeP‐CoMoP hierarchical nanostructures (HNSs) were successfully fabricated through a facile phosphorization strategy using Co−Mo‐Fe HNSs as precursors, and directly served as electrocatalysts for alkaline hydrogen evolution. Owing to the well‐defined hierarchical nanostructures with high charge‐transfer efficiency, favourable conductivity and good electrolyte infiltration, the FeP‐CoMoP HNSs display an excellent HER performance in alkaline media.